Analysis of induced pluripotent stem cell clones derived from a patient with mosaic neurofibromatosis type 2. Issue 6 (18th February 2022) - Ishi, Yukitomo; Era, Takumi; Yuzawa, Sayaka; Okamoto, Michinari; Sawaya, Ryosuke; Motegi, Hiroaki; Yamaguchi, Shigeru; Terasaka, Shunsuke; Houkin, Kiyohiro; Fujimura, Miki
Abstract: The diagnosis of mosaicism is challenging in patients with neurofibromatosis type 2 (NF2) subset due to low variant allele frequency. In this study, we generated induced pluripotent stem cells (iPSCs) were generated from a patient clinically diagnosed with NF2 based on multiple schwannomas, including bilateral vestibular schwannomas and meningiomas. Genetic analysis of the patient's mononuclear cells (MNCs) from peripheral blood failed to detect NF2 alteration but successfully found p.Q65X (c.193C>T) mutation in all separate tumors with three intracranial meningiomas and one intraorbital schwannoma, and confirming mosaicism diagnosis in NF2 alteration using deep sequencing. Five different clones with patient‐derived iPSCs were established from MNCs in peripheral blood, which showed sufficient expression of pluripotent markers. Genetic analysis showed that one of five generated iPSC lines from MNCs had the same p.Q65X mutation as that found in NF2 . There was no significant difference in the expression of genes related to NF2 between iPSC clones with the wild‐type and mutant NF2 . In this case, clonal expansion of mononuclear bone marrow‐derived stem cells recapitulated mosaicism's genetic alteration in NF2. Patient‐derived iPSCs from mosaic NF2 would contribute to further functional research of NF2 alteration.